The downside of downsizing: Persistence of racial disparities following state prison reform. (October 2022) - Lerman, Amy E; Mooney, Alyssa C
Nationwide, prison populations have declined nearly 5% from their peak, and 16 states have seen double-digit declines. It is unclear, though, how decarceration has affected racial disparities. Using national data, we find substantial variation in state prison populations from 2005–2018, with increases in some states and declines in others. However, although declines in the overall state prison population were associated with declines for all groups, states with rising prison populations experienced slight upticks in prison rates among the white population, while rates among Black and Latinx populations declined. As a result, greater progress in overall decarceration within states did not translate to larger reductions in racial disparities. At the same time, we do not find evidence that a decline in prison populations is associated with a rise in jail incarceration for any racial/ethnic group. In additional exploratory analyses, we suggest that recent incarceration trends may be driven by changes in returns to prison for probation and parole violations, rather than commitments for new crimes. Our results make clear that while efforts to reverse mass incarceration have reduced the size of prison populations in some states, they have not yet made substantial progress in resolving the crisis of race in American criminal justice.